Kajian Genolinguistik dalam Analisis Kesalahan Penggunaan Ejaan Bahasa Tulis di Media Sosial Facebook - Musa Hefer Smas; Meggy Merlin Mokay (LP. Ma'arif Janggan Magetan, 2022)
This study aims to look at the study of genolinguistics in spelling mistakes on Facebook as a social media. The research method used is a case study. This research uses orthographic data analysis techniques. The determining orthographic data analysis technique is to see what is right and wrong. The results of the study (1) found that some of the Papuan generation made mistakes in writing vocabulary on Facebook by subtracting and adding the letters h, n, g (n/g). The results of the identification of errors in writing the letters h, n and g in the status vocabulary on Facebook, found that there were 101 vocabularies for the letter h and 62 vocabularies for the letter g (ng or). (2) Errors in writing the letters h, n and g (ng or) occur because of the influence of the innate nature of language that becomes a habit. Writing errors that become a habit in written language on social media status are influenced by Genetics of Family Relations, Social Kinship Association, Domicile Region and Regional Language Dialect Interference, Papuan Malay Language Variety Interference, and Educational Level. (3) The innate nature that has become a habit of spoken language into written language. Some generations of Papuans often do the pronunciation by reducing and adding the sounds of the letters h, n and g (ng/ŋ).